STATE-BUILDING vs. RESOURCE MANAGEMENT (The Case of Azerbaijan and Its Oil Fund Management) - KALYONCU, Mehmet (CENTRAL ASIA AND THE CAUCASUS, 2006)
Dependency is what the state elite, be it government officials or the political leader, of the developing countries at the periphery make of it. That is, whether the economic ties of the periphery with the center lead to modernization and prosperity or dependency and underdevelopment depends on the development policies of the periphery states. In that sense, analysis of the economic policies of a given government gives us insights about whether the country is heading to democracy and prosperity, or authoritarianism and underdevelopment. Such analysis is especially crucial for countries undertaking state-building process and development of their vast natural resources simultaneously. Azerbaijan provides a perfect example Multinational corporations may lead either to satellite-center relationship and hence underdevelopment of the periphery, or to prosperity and modernization at the periphery. What determines the outcome out of these two is the attitude of the government, specifically of the leader, of the host country. I argue that the dependency is what the state elite, be it government officials or the political leader, of the developing countries at the periphery make of it. That is, whether the economic ties of the periphery with the center lead to modernization and prosperity or dependency and underdevelopment depends on the development policies of the periphery states. In other words, ceteris paribus1 the state has the control to determine the legal framework in accordance with which the foreign capital operates within the country. As such, it can control the impact of the foreign capital on economic development of the country. This is especially so in extractive industries. Since the extraction site has a fixed location, the resources are not easily transferable and the state rather than private parties has the ultimate control over the extraction sites, the government can be very demanding in terms of establishing the operative regulations of the foreign extraction and related companies. There are several crucial tasks that the host countries need to fulfill in order to have the multinational companies contribute to their overall development. First, they need to understand what they can expect from the multinational corporations and what they cannot, in other words, they need to accept the multinational corporations as self-interested actors working to maximize the profit of their shareholders. As the commercial director of the BP, which is the largest shareholder and operator of the oil and gas related projects in Azerbaijan, notes, “we are not an aid agency or a charity. Our purpose is to create wealth on behalf of our shareholders. Our interests will thrive if the societies in which we invest also thrive.”2 Namely, the multinational corporations and the host country may first have mutual benefits and can achieve these benefits as long as they cooperate. Second, they need to grow a middle class as large as possible by involving the local small businesses in the extraction related industries. Third, they need to grow a human capital by gaining know-how about the industry. Fourth, they must build institutions independent of political influence and protected by the constitution. These institutions must oversight the activities related to the development of the natural resources. Fifth, they must accumulate the natural resource income in a fund which is under the control of not the government and hence the president but of the private management council. Sixth, they must transform the income into long-term income-generating mechanisms for the national economy. The quintessential to managing natural resource wealth, which is predominantly oil in the Azerbaijan case, is to keep in mind that that particular resource sooner or later will have depleted. Therefore, in order to maintain the pace of the economy based on the natural resource development, the government must ensure that the resource income is being invested in new institutional arrangements and income-generating mechanisms that are capable of replacing the depleting natural resources. Joseph Stiglitz suggests that the government must build natural resource fund with stabilization and savings functions so that it can prevent the negative impacts of oil price volatility on the domestic economy. Lastly, they must ensure maximum transparency, accountability, and the involvement of the citizens in the decision-making process about how to spend the natural resource income.